Alcohol abuse among adolescents and suicide risk - is there a correlation? - Kinga Szopińska; Magdalena Graca; Karolina Korta; Anna Szeliga; Agata Szostak; Karolina Oluszczak; Liliana Dyląg; Maria Janina Śmigielska-Mikołajczyk; Konrad Wawszkowicz; Weronika Łowicka (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Adolescent alcohol abuse is a critical public health issue with far-reaching consequences for individual development and societal well-being. Adolescent alcohol consumption poses significant health risks, particularly due to its effects on brain development and its association with increased suicide risk. Purpose of the work: This study aims to investigate the relationship between alcohol abuse and suicide risk in adolescents. Materials and methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the search terms including the following keywords: alcohol abuse/ alcohol abuse in adolescence/ alcohol consumption in adolescence/ alcohol abuse and suicide risk in adolescence/ suicide risk factors in adolescence/ suicidal tendencies among teenagers. Conclusions: Adolescent alcohol abuse has profound implications for brain development and mental health, significantly increasing the risk of suicide. Effective public health strategies, including early intervention, education, and strong support systems, are essential to mitigate these risks and promote healthier environments for young individuals. Addressing the underlying causes of alcohol abuse and providing targeted support can reduce its long-term consequences and improve adolescent well-being.